To Punish or to Restore: How Children Evaluate Victims' Responses to Immorality - Liu, Xin; Yang, Xin; Wu, Zhen (Frontiers in Psychology, 2021)
Punishment is important for deterring transgressions and maintaining cooperation, while restoration is also an effective way to resolve conflicts and undo harm. Which way do children prefer when evaluating others' reactions to immorality? Across four experiments, Chinese preschoolers (aged 4–6, n = 184) evaluated victims' different reactions to possession violations (i.e., punishing the perpetrator or restoring the belongings). Children evaluated restorative reactions more positively than punitive ones. This tendency to favor restoration over punishment was influenced by the degree of punishment, with more pronounced patterns observed when punishment was harsher (Experiments 1–3). Indeed, when different degrees of punishment were directly contrasted (Experiment 4), children viewed victims who imposed milder punishment (“steal one object, remove one or two objects”) more positively than those who imposed harsh punishment (“steal one object, remove three objects”). These patterns were especially manifested in preschoolers who chose restoration when being put in the victim's situation, suggesting a consistency between evaluations and behaviors. Taken together, the current study showed that children prioritize protecting the victim over harshly punishing the perpetrator, which suggests an early take on the preferred way to uphold justice.